Upin & Ipin: Promoting malaysian culture values through animation - Abdul Ghani, Dahlan Bin (Historia y Comunicación Social, 2015)
Malaysian children lately have been exposed or influenced heavily by digital media entertainment. The rise of such entertainment tends to drive them away from understanding and appreciating the values of Malaysian culture. Upin and Ipin animation has successfully promoted Malaysian folklore culture and has significantly portrayed the art of Malaysian values including Islamic values by providing the platform for harmonious relationship among different societies or groups or religious backgrounds. The focus of this research is to look into the usage of Malaysian culture iconic visual styles such as backgrounds, lifestyles, character archetypes and narrative (storytelling). Therefore, we hope that this research will benefit the younger generation by highlighting the meaning and importance of implicit Malaysian culture.
Keywords: Upin and Ipin; animation; narrative; folklore; culture; character archetypes